2017
DOI: 10.1002/ijc.31179
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel fusion gene HMGA2‐EGFR in glioblastoma

Abstract: Glioblastoma is one of the most malignant forms of cancer, for which no effective targeted therapy has been found. Although The Cancer Genome Atlas has provided a list of fusion genes in glioblastoma, their role in progression of glioblastoma remains largely unknown. To search for novel fusion genes, we obtained RNA-seq data from TGS-01 human glioma-initiating cells, and identified a novel fusion gene (HMGA2-EGFR), encoding a protein comprising the N-terminal region of the high-mobility group AT-hook protein 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…Fusion of HMGA2 with epidermal growth factor receptor gene (EGFR) from 7p11 gives rise to a fusion gene which encodes a chimeric HMGA2-EGFR protein; this was reported in a single case of glioblastoma (71). An in-frame fusion transcript of HMGA2 with Yes1-associated transcriptional regulator gene (YAP1) from 11q22 was reported in an aggressive angiomyxoma (72).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fusion of HMGA2 with epidermal growth factor receptor gene (EGFR) from 7p11 gives rise to a fusion gene which encodes a chimeric HMGA2-EGFR protein; this was reported in a single case of glioblastoma (71). An in-frame fusion transcript of HMGA2 with Yes1-associated transcriptional regulator gene (YAP1) from 11q22 was reported in an aggressive angiomyxoma (72).…”
Section: Discussionmentioning
confidence: 99%
“…Grep Tumorigenic properties were found for the HMGA2-LPP and HMGA2-EGFR fusion proteins, whereas functional studies have not been performed to test for effects of the HMGA2-YAP1 chimera (54,(70)(71)(72). HMGA2-LPP transforms 3T3 mouse embryonic fibroblasts (54).…”
Section: Casementioning
confidence: 99%
“…A novel fusion gene HMGA2-EGFR has been identified by Komuro et al ( 23 ). It could encode a protein comprising the N-terminal region of the high-mobility group AT-hook protein 2 (HMGA2, chromosome location 12q14.3) fused to the C-terminal region of EGFR.…”
Section: Main Targetable Gene Fusions In Malignant Gliomasmentioning
confidence: 99%
“…High-mobility group AT-hook 2 (HMGA2) is a transcription factor that belongs to the non-histone chromosomal high-mobility group (HMG) protein family and is typically correlated with gene expression by remodeling the chromatin state [ 16 ]. Changes of HMGA2 have been investigated in human mesenchymal tumors, pleomorphic adenomas, and OS [ 17 ]. A previous study indicated that miR-490-3p expression was negatively correlated with HMGA2 in OS, and the tumor-suppressed function of miR-490-3p could be reversed by overexpression of HMGA2 in OS cells [ 18 ].…”
Section: Introductionmentioning
confidence: 99%